2015
DOI: 10.1007/8904_2014_403
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Increasing Doses of Nitisinone in the Treatment of Alkaptonuria

Abstract: Alkaptonuria is an autosomal recessive disease involving a deficiency of the enzyme homogentisate dioxygenase, which is involved in the tyrosine degradation pathway. The enzymatic deficiency results in high concentrations of homogentisic acid (HGA), which results in orthopedic and cardiac complications, among other symptoms. Nitisinone (NTBC) has been shown to effectively treat alkaptonuria by blocking the conversion of 4-hydroxyphenylpyruvate to HGA, but there have been concerns that using doses higher than a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…13,24,25,[101][102][103][104] The drop in HGA concentrations was rapid, with approximately 60% decrease in circulating HGA within 48 hours on 2 mg dose (unpublished data), and thus is an efficacious treatment. 101 Six clinical trials have been undertaken on the use of nitisinone to treat AKU.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…13,24,25,[101][102][103][104] The drop in HGA concentrations was rapid, with approximately 60% decrease in circulating HGA within 48 hours on 2 mg dose (unpublished data), and thus is an efficacious treatment. 101 Six clinical trials have been undertaken on the use of nitisinone to treat AKU.…”
mentioning
confidence: 94%
“…101 Six clinical trials have been undertaken on the use of nitisinone to treat AKU. 24,25,86,[102][103][104] The first study was an early dose ranging study in two older women with AKU. 102 An open-label, single-center study of 9 AKU patients showed that the dose required to decrease HGA significantly was up to 30-fold lower than that used in treating HT1.…”
mentioning
confidence: 99%
See 3 more Smart Citations